Estetika UGC Low-Fidelity dan Konstruksi Autentisitas Merek di Media Sosial - Susanto, Rofian Dedi (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Digital transformation has shifted marketing communication from brand-centered messaging to participatory meaning-making, where consumers actively co-construct brand perceptions. This study analyzes the use of low-fidelity User-Generated Content (UGC) on Instagram @scarlettofficial to build brand authenticity, identifies key visual and textual markers of low-fidelity aesthetics, and examines how audience interaction contributes to the social construction of authenticity. Using a qualitative netnographic approach, 60 low-fidelity UGC posts and audience comments were observed. Findings show that natural lighting, handheld camera movements, genuine expressions, informal language, reflective captions, and emojis serve as authenticity markers. Audience engagement fosters co-construction of authenticity through emotional resonance, comparative cognition, and normative responses. Low-fidelity UGC is thus a participatory communication strategy that enhances credibility, emotional closeness, and perceived authenticity in social media marketing.